Language and religion : a journey into the human mind - Downes, William (Cambridge University Press, 2012)
"Language and Religion offers an innovative theory of religion as a class of cultural representations, dependent on language to unify diverse capacities of the human mind. It argues that religion is widespread because it is implicit in the way the mind processes the world, as it determines what we ought to do, practically and morally, to achieve our goals. Focusing on the world religions, the book relates modern cognitive theories of language and communication to culture and its dissemination. It explains basic features of religion such as the supernatural, the normative, abstract and ideal theological concepts such as 'God', and religious feeling. It develops a linguistic theory, based on how utterances are understood, of metaphysical and moral 'mysteries' and their key role in thought and action. It shows how such concepts gain strength in the light of their successful use, and when tempered by criticism, can also have genuine authority"-- Provided by publisher